Pandoraea pnomenusa Superinfection in a Patient with SARS-CoV-2 Pneumonia: First Case in the Literature - Diego Alejandro Cubides-Diaz; Natalia Muñoz Angulo; Daniel Augusto Martin Arsanios; Ana Lucia Ovalle Monroy; Daniel Ricardo Perdomo-Rodriguez; Maria Paula Del-Portillo (MDPI AG, 2022)
Pandoraea pnomenusa is a Gram-negative bacterium of the Pandoraea genus and is mainly associated with the colonization of structurally abnormal airways. During the COVID-19 pandemic, many microorganisms have been associated with coinfection and superinfection in SARS-CoV-2 pneumonia, but so far, no coinfection or superinfection by P. pnomenusa has been reported. We present the first case describing this association in a previously healthy patient. Clinical manifestations, treatment, and outcomes are shown.